Effectiveness of Using Natural Coagulants in Making Koro Pedang Tofu - Sudarmin, Nur Fajriani Arifuddin; Syam, Husain; Sukainah, Andi (Agricultural Technology Education Study Program, 2024)
Tofu is a processed food product whose raw material uses soybeans. The purpose of the research conducted was to determine the effectiveness of the addition of natural coagulants in the form of lime and starfruit in the manufacture of tofu with substitution of koro pedang. The research method used is a quantitative method using a two-factor factorial design and three replications. The concentration of natural coagulants in this study were 5% and 7% lime and 20% and 40% starfruit wuluh. This study produced water content values ranging from 70.53-82.31%, cyanide acid levels ranged from 5.77-8.95 mg/kg, protein levels ranged from 9.53- 16.30% and hedonic divided into two, namely hedonic quality in raw tofu includes color ranging from 3.25-3.56%, texture ranging from 3.21-3.68% and aroma ranging from 3.19-3.67% while hedonic quality in fried tofu includes color ranging from 3.20-3.57%, texture ranging from 3.08 - 3.59%, aroma ranging from 3.39-3.73% and taste ranging from 3.43-3.77%. Furthermore, the resulting normality test shows that the data is normally distributed with the Shapiro-Wilk value obtained which is> 0.05 and the homogeneity test shows a significant value which is> 0.05.